What drive the changes in China's energy consumption and intensity during 12th Five-Year Plan period? - Yan, Junna; Su, Bin (Energy policy, 2020)
During the 12th Five-Year Plan Period (2011–2015), the Chinese government has released a series of energy conservation plans to launch and deepen the transition in the energy use. Particularly, the dual control of the energy consumption and energy intensity was firstly emphasized. This paper intends to explore the targeted and effective energy policy implications through investigating the drivers of changes in energy consumption/intensity of China during the 12th Five-Year Plan Period. Under the input-output framework, the embodied energy consumptions/intensities by final demand category were estimated at aggregate/sector level and the total energy consumption/intensity was decomposed using the additive/multiplicative structural decomposition analysis. Among the final demand categories, China's energy consumption/intensity was mainly contributed by the investment, followed by the household consumption. According to the SDA results, China's total energy consumption increased by 28.8%, of which the energy intensity effect and the investment effect were the most retardant and accelerator, respectively. At the same time, China's total aggregate energy intensity decreased by 16.0%, of which the energy intensity effect and the household consumption effect were the most retardant and accelerator, respectively. In detail, the key sectors with respect to the critical effects were picked out. Above all, policy implications are discussed for achieving the energy goals during the 13th Five-Year Plan Period and launching the energy revolution during the 14th Five-Year Plan Period. •China's energy and intensity changes are studied using the input-output framework.•Aggregate embodied intensity is used for energy intensity analysis.•Both additive and multiplicative decomposition analyses are adopted in the analysis.•Investment and household consumption are major driving forces to the changes happened in China.•Policy implications are discussed for China based on the analysis of its 12th Five-Year Plan period.